Limiting factors for the success in alpine skiing - Ropret, R. (Facta Universitatis: Series Physical Education and Sport, 2015)
For success in skiing, it is essential to know the characteristics of the kinematics and motion dynamics, morphological, functional and motor characteristics of skiers. Skiing is characterized by movements down the slope during which a skier overcomes inertia forces of approximately three times the weight of his own body. The movements of moderate speed dominate mainly in terms of isometric and eccentric contractions. The intensity of the forces of the engaged muscle groups, positions of body segments, amplitude and speed of movements in different joints vary depending on the competitive discipline. The knowledge of the mentioned characteristics of skiing is important for quality planning of training, choice of exercises and training methods. The choice of tests to assess this ability should be based on the knowledge gained by analyzing the characteristics of the movement of skiers. This paper analyzes the basic morpho-functional, kinematic and dynamic characteristics of skiing